Analisis Motivasi Kerja Dan Kompetensi Guru - Boby Yasman; Susy Pransiska; Muhammad Rafii (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
Work motivation and teacher competence in an educational institution are interrelated and contribute to an institutional mission. SMA S Nurul Yaqin which is under a certain foundation has interesting dynamics to observe, analyze and explain regarding the motivation of teachers to work and their competencies. This research was conducted with the aim of analyzing work motivation and its relationship with teacher competence as educators. The type of approach in this research is qualitative. By determining the research subject using purposive sampling technique. Data were collected through interviews, observation and documentation from various primary and secondary data sources. Then the data were analyzed by data reduction techniques, data presentation, and drawing conclusions. This study obtained the results that each teacher has different motivations and main competencies. However, almost all of the informants realized that work motivation and teacher competence were positively, significantly, and correlatively related. Because after all, the motivation and competence of teachers and performance in general are intertwined. This study recommends that schools institutionally facilitate various programs to support the main competencies of each teacher, such as professionalism, individual and social. However, teachers are also required to take the initiative as individuals in accessing information